Effects of Acupuncture on Oxidative Stress Amelioration via Nrf2/ARE-Related Pathways in Alzheimer and Parkinson Diseases. (27th April 2021) - Huang, Teng-I; Hsieh, Ching-Liang
Abstract : Oxidative stress is responsible for the pathogeneses of various diseases. Mitochondrial dysfunction, impaired DNA repair, and cellular damage followed by oxidative stress contribute to neurodegenerative diseases, such as Alzheimer disease (AD) and Parkinson disease (PD). Acupuncture is a traditional therapy that has been practiced for >3000 years in Asia. Many studies have demonstrated that acupuncture has notable antioxidative, anti-inflammatory, and antiapoptotic effects. However, the exact mechanism remains unclear. Nuclear factor erythroid 2-related factor (Nrf2) is crucial in regulating the redox equilibrium. Activated Nfr2 translocates into the nucleus, binds to the antioxidant response element (ARE), and initiates antioxidative enzyme transcription. In this review, we demonstrated the effects of acupuncture on oxidative stress amelioration in AD and PD animal models through Nrf2/ARE pathway activation and Nrf2/ARE-related pathway regulation. Thus, acupuncture could be a therapeutic option for AD and PD.